Fuzzy-controlled humidity variation by silica gel and nitrogen gas in an atmospheric chamber - Ghahraei, Ali; Md Yunus, Nurul Amziah; Abdul Halin, Izhal; Sulaiman, Nasri (Universiti Putra Malaysia Press, 2017)
Controlled humidity environment is of significance in many scientific researches and experiments. In most laboratory-scale atmospheric chambers, an electrical temperature-based control system is used to adjust humidity. Since these chambers are not affordable in every laboratory, other low cost chambers using nitrogen gas or silica gel are used to adjust humidity. In this paper, a mechanism was developed to control the relative humidity in closed lab-scale chambers. Humidification is done by spraying water through a blower fan while de-humidification is by pumping air through silica gel as well as nitrogen gas injection. A Mamdani type fuzzy controller was designed to control the components and relative humidity. The results show the proposed system and controller can adjust and maintain relative humidity from 41% to 100% with maximum overshoot of 1% and the maximum range of error of steady state of 1.2 %.